The Influence of Work Motivation and Workload on Employee Performance with Job Satisfaction as a Mediation Variable - Umi Laila Safitri; Bambang Widagdo; Khusnul Rofida Novianti (Universitas Muhammadiyah Malang, 2022)
This study aims to determine whether work motivation and workload have an influence on employee performance with job satisfaction as a mediating variable on CV. Indah Cemerlang Singosari. The type of research used in this research is the quantitative method. While the data analysis technique used is the Partial Least Square – Structural Equational Model (PLS-SEM). The sample in this study were all employees of the production division at CV. Indah Cemerlang Singosari, totaling 44 people using a saturated sampling technique. Based on the result of research that has been carried out using the Partial Least Square – Structural Equational Model (PLS-SEM), shows that work motivation has a significant effect on job satisfaction. While the workload has no significant effect on job satisfaction. Work motivation and job satisfaction have no significant effect on employee performance. Workload has a significant effect on employee performance. Job satisfaction does not mediate the effect of work motivation and workload on employee performance.